GEORGIE – Componentes GEOgráficos como Recomendações para Governança da Informação Efetiva em wikimapas - Borges , Carlos Eduardo Liedtke; Reis, Me. Adriana Neves dos (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2017: Anais Estendidos do XXIII Simpósio Brasileiro de Sistemas Multimídia e Web, 2017)
Nowadays it’s observable the increase of web solutions and collaborative systems based on wikimaps (WikiMapia.org, Colab.re, Google My Maps etc.). The development of the Buracos Monitor project helped to identify significant challenges of Information Governance, related to this kind of applications, motivating the research on the subject. An analysis of similar systems is performed, from the point of view of the 3C Collaboration Model and Groupware Engineering, to identify common practices and components of this type of solution. The knowledge acquired, as a result of this analysis and exploratory research, was compiled and presented as the GEORGIE framework. A set of tools and components are listed and described, and a new analysis is presented from the point of view of Information Governance. The validation method of this research was focused on academic acceptance with specialists, and a case study is exposed, describing the use of the framework in the implementation of improvements to the system Buracos Monitor. Finally, It’s proposed that GEORGIE, the result of this research, as fundamental and introductory content for analysts, developers and interested in develop systems of this family, and for conducting similar research.